Assessment of Left Ventricular Volumes and Function by Real Time Three-Dimensional Echocardiography in a Pediatric Population: A TomTec versus QLAB Comparison. - Hascoët S; Brierre G; Caudron G; Cardin C; Bongard V; Acar P (Echocardiography, 2010)
Background: Three-dimensional echocardiography (3DE) allows accurate calculation of ventricular volumes despite a remaining geometric assumption on the ventricular shape. Few studies involving full volume reconstruction software have been performed on children. Our aim was to compare the left ventricular (LV) volume measurements obtained with the most used 3D analysis software in a pediatric population. Methods: Fifty patients (median age: 9.5 years) without cardiac disease were included in the study. 3DE was performed with the X4-2 or X7-2 matrix probe (ie33, Philips). The LV volume analysis was performed with QLAB 6.0 (semiautomated border detection) and TomTec 4D LV (primary manual tracking with semiautomated border detection). Results: TomTec analysis feasibility amounted to 94% whereas QLAB analysis feasibility only reached 80% (P = 0.037). The analysis time was shorter with QLAB than TomTec (5 ± 2 versus 6 ± 3 minutes, P < 0.05). The stroke volume, end diastolic and end systolic LV volume measurements performed on the 40 patients were strongly correlated (r > 0.97; P < 0.0001) with minimal bias. The LV ejection fraction was well correlated (r = 0.79; P < 0.0001). Conclusion: 3D LV volume quantification is feasible either by using manual or automated reconstruction software in a normal pediatric population. LV Measurements are well correlated. Differences in volume reconstruction algorithms provide specific software performance characteristics. TomTec is a more feasible method but requires a longer analysis time. Further studies are needed to validate the accuracy of the method to calculate enlarged LV volumes in patients with congenital heart diseases. (Echocardiography 2010;27:1263-1273)